Satisfaction of Students Regarding Communication with Healthcare Providers at College Health Services - Niraula, Kushal; Karki, Tej Bahadur; Chaudhary, Rajeshwer Prasad; Acharya, Bhumi Raj (International Journal of Atharva, 2024)
This quantitative descriptive study focuses on how satisfied college students are with communication from medical professionals at Atharva Business College in Nepal. The study was conducted from April 2023 to June 2023. The study includes 89 students, mostly female, aged 18 to 29, who received medical assistance at the on-campus Student Health Centre. Participants completed a questionnaire survey to score their satisfaction with several aspects of provider communication. The results show a high overall acceptance rate, with specific areas such as the greeting process, respectful treatment, and interest in patients' suggestions garnering positive comments. Most participants reported that they had excellent communication about their health problems, were involved in decision-making, and understood medical information. The findings highlight the importance of excellent provider communication in improving patient outcomes and satisfaction in a campus healthcare setting.